2008
DOI: 10.1248/yakushi.128.1067
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Promyelocytic Leukemia Protein in the Ethanol-induced Apoptosis in Mouse Embryo Fibroblasts

Abstract: The promyelocytic leukemia (PML) gene is a tumor suppressor gene associated with cell apoptosis, cell proliferation, and senescence. However, the role of PML in the ethanol-induced apoptosis is not fully-known. In this study, using wild-type mouse embryoˆbroblasts (MEF) and PML null MEF cells, we found that (1) ethanol (100 mM and 200 mM) could obviously induce apoptosis of wild-type MEF cells, whereas, in PML null MEF cells, the pro-apoptotic function of ethanol was partially blocked; (2) the expression level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Despite this observation, and consistent with our data, the Dnmt-1 transcript was down-regulated by alcohol in both neural stem cells [60] and rat sperm [61]. Numerous studies have reported the effects of ethanol exposure on gene expression [29,6269]. Intriguingly, in the present study, ethanol stimulated the expression of the genes encoding the “ de novo ” methyltransferases (DNMT-3a and -3b), but not the “maintenance” methyltransferase (DNMT-1).…”
Section: Discussionsupporting
confidence: 88%
“…Despite this observation, and consistent with our data, the Dnmt-1 transcript was down-regulated by alcohol in both neural stem cells [60] and rat sperm [61]. Numerous studies have reported the effects of ethanol exposure on gene expression [29,6269]. Intriguingly, in the present study, ethanol stimulated the expression of the genes encoding the “ de novo ” methyltransferases (DNMT-3a and -3b), but not the “maintenance” methyltransferase (DNMT-1).…”
Section: Discussionsupporting
confidence: 88%
“…However, these results do suggest that in MEFs that the Plk4 promoter may be a target for regulation by methylation in response to metabolic stress. This idea is supported by the fact that chronic alcohol exposure of MEFs has been shown to increase levels of reactive oxygen species (ROS) [30], as well as increase levels of p53 and p53 downstream targets such as p21 [31]. Interestingly, consistent with this p53 has been shown to indirectly repress Plk4 expression via HDAC in response to stress [22].…”
Section: Resultsmentioning
confidence: 97%
“…There are a number of discrepancies in the literature regarding the response of cells to EtOH, particularly regarding cell proliferation and apoptosis. Studies with fibroblasts isolated from skin and mouse embryos have reported decreases in proliferation and apoptosis when exposed to EtOH (Ranzer et al., ; Wang et al., ). The amount of EtOH used for treatment may be important as well as the origin of the fibroblasts as another study utilizing embryonic fibroblasts and a smaller concentration of EtOH reported no apoptosis or fibrogenic effects caused by EtOH alone (Brenner and Chojkier, ).…”
Section: Discussionmentioning
confidence: 99%